Promotion of Organizational Learning from the Education Committees of Transport Cooperatives (Global Journal of Management and Business Research, 2022)
The initial purpose of the study is to answer the question: What type and styles of learning are promoted in the cooperative transport sector from the work of the education committees? Therefore, from the theoretical foundations, the project achieved compliance with the general objective, focused on knowing the types, styles and characteristics of the organizational learning promoted by the transport cooperatives through the management of the education committee, therefore, a quantitative methodology was applied, applying the instrument to Directors of the four active education committees in transport cooperatives in the municipality of Oca#xF1;a. Finally, it is obtained with the results that the most predominant organizational learning is corrective and adaptive, and is represented in the solidarity institutions.
Keywords: organizational learning; intellectual capital; cooperative; education committees